FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN DOMESTIK KE CAFE EL LAGO, KINTAMANI, BALI - Ridwan, Rina El Diana; Mananda, I GPB. Sasrawan; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
Pandemic has a major impact on the tourism sector in Bali, many of tourist attractions are closed due to the effect of Covid-19 and  some of it turn to a restaurant or cafe business, one of popular cafe is Cafe El Lago which has a unique buildings and located near Batur mountain and it is suitable as a place for relaxation. The purpose of this study is to find out the characteristics and factors that influence the decision of domestic tourists to visit Cafe El Lago. The sample in this study is 100 domestic tourists with sampling techniques is purposive sampling. Data was taken in this study by using observation techniques, questionnaires, documentation and literature studies. Data were analyzed using validity tests, reliability tests and factor analysis techniques.  The results showed that there are 6 variable factors that affectingdomestic tourists from 23 indicators. The six (6) factors have eigenvalue > 1 with a cumulative eigenvalue value of 63,32%.The most dominant factor from overal factors is service factor has an eigenvalue value of 6,99 with a total variance of 16,71% consists of six forming indicators consisting of (1) speed, (2) friendliness. (3) accuracy, (4) directions. (5) quality, (6) availability of transportation and this factor is the main factor that affect domestic tourists visiting Cafe El Lago Batur Selatan, Kintamani, Bangli, Bali.